Features of the credit risk management of commercial banks in Russia in terms of financial instability (Путеводитель предпринимателя, 2020)
The global financial crisis has shown the existence of certain problems of the Russian banking system, which are an obstacle to the successful development of the credit business. Ineffective management of credit risk of financial instability is one of the main problems of Russian commercial banks.